Expression of Thrombomodulin, Calretinin, Cytokeratin 5/6, D2–40 and WT-1 in a Series of Primary Carcinomas of the Lung: An Immunohistochemical Study in Comparison with Epithelioid Pleural Mesothelioma. Issue 5 (September 2014) - Comin, Camilla E; Novelli, Luca; Cavazza, Alberto; Rotellini, Matteo; Cianchi, Fabio; Messerini, Luca
Aims and Background: A number of immunohistochemical markers have been suggested as useful in the positive diagnosis of epithelioid mesothelioma. The most widely used mesothelioma markers are thrombomodulin, calretinin, cytokeratin 5/6, D2–40 and WT-1. Numerous investigations have demonstrated their variable sensitivity and specificity in differentiating epithelioid mesothelioma from lung adenocarcinoma. However, data on the expression of these markers in other types of lung carcinomas are very limited. We evaluated the expression of these markers in a series of 172 primary carcinomas of the lung and in 75 epithelioid pleural mesotheliomas. Results: Thrombomodulin expression was found in squamous cell carcinomas (71%), small cell lung carcinomas (11%), adenocarcinomas (4%), large cell carcinomas (50%), large cell neuroendocrine carcinomas (25%) and in sarcomatoid carcinomas (10%). Calretinin expression was common in small cell lung carcinomas (44%) and large cell neuroendocrine carcinomas (25%), less common in squamous cell carcinomas (20%), rare and focal in adenocarcinomas (4%) and sarcomatoid carcinomas (10%). Cytokeratin 5/6 was expressed in most of the squamous cell carcinomas (94.5%). Immunoreactivity was also found in large cell carcinomas (50%), sarcomatoid carcinomas (30%) and rarely in adenocarcinomas (4%). D2–40 was consistently expressed in squamous cell carcinomas (42%). Focal immunoreactivity was found in adenocarcinomas (3%). WT-1 was focally present in one (2%) squamous cell carcinoma. Conclusions: These results indicate that some of the most commonly used mesothelioma markers may react with different types of primary lung carcinomas. These data should be taken into consideration especially when dealing with small biopsy fragments and poorly differentiated tumors.